(untitled) (Singaporean Journal of Business Economics and Management, 2013)
The aim of this study was to investigate the impact of online service quality on customer satisfaction in banks of Guilan. Standard model of this article was elected based on Yang and others (2004). Six factors including reliability, responsiveness, competence, ease of use, security and Product portfolio are identified as dimensions of online services quality. In the present study, multiple and linear regression was measured the impact of online service quality on satisfaction. The results showed that all 6 factors of online service quality had effect on customer satisfaction of public banks of Guilan.